THE INFLUENCE OF SOCIAL MEDIA MARKETING ON BRAND AWERENESS AND THEIR IMPACT ON PURCHASE DECISION (Case Study: English Village of Jogja in Bantul Regency) - Abdul Mujib; Dimas Wibisono; Toufan Aldian Syah (DAS Institute, 2023)
The purpose of this study was to determine the effect of social media marketing with brand awareness, the effect of brand awareness on purchase decisions, and the influence of social media marketing through brand awareness on purchase decisions. This type of research is quantitative research with analytical observational methods and cross sectional design. The sampling technique used is the purposive sampling technique with the Slovin formula. The number of samples is 91 respondents. Hypothesis testing using Regression Test and Path Analysis Test. There is an influence between social media marketing and brand awareness, there is an influence of brand awareness with purchase decisions, and there is an influence of social media marketing through brand awareness on purchase decisions.There is an influence between social media marketing and brand awareness, there is an influence of brand awareness with purchase decisions, and there is an influence of social media marketing through brand awareness on purchase decisions.